Survey on Effect of Multimodal Interface on Senior Citizen (International Journal of Engineering and Computer Science, 2018)
Multimodal interface is designed within CAMI in which an Artificial Intelligent ecosystem integrates the main functionalities of AAL (Ambient Assisted Living) systems for senior citizen, which are its target users to fulfill their needs. It supports numerous languages. It can process both gesture and speech commands. It must work on different devices and adapt to any screen size. The interface is developed using HTML5, JavaScript, CSS3 and integrates Google Speech Service along with other services